Transforming EFL Instruction: A Systematic Review of Chatbot Integration in English Language Learning - Made Natya Pradnya Iswari; Santosa, Made Hery; Indrayani, Luh (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
There are important areas that have not been fully investigated. The use of chatbots to improve students' language learning abilities presents various advantages and obstacles. This study explores the integration of Chatbots in English language instruction for EFL learners, focusing on their impact on learning implementation experiences, advantages, and limitations. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards, the research reviewed articles from 2019 to 2024 to ensure a comprehensive analysis. A total of 998 publications were identified through Google Scholar, with search terms such as "chatbot," "AI chatbot," and "Chatbot implementation among EFL learners in English language learning." After an extensive screening process, including duplicate removal, inclusion, and exclusion criteria, 10 empirical, open-access studies were selected for review. The findings reveal that ChatGPT significantly enhances writing, grammar, and vocabulary skills by providing immediate and personalized feedback. It also fosters engagement and motivation while supporting cultural exploration and intercultural competence. However, limitations include reduced efficacy in developing speaking and listening skills, technical challenges, and ethical concerns. The study concludes that while ChatGPT is a valuable tool, it should complement, not replace, traditional teaching methods to ensure a balanced and effective learning experience.